Comparative analysis of emotion recognition methods - Zaman, Mustafa; Islam, Iftekhairul (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.